A composite structure metal-ceramic light-to-heat conversion coating and preparation method thereof
The preparation of nanocomposite structural metal cermet photothermal conversion coatings through multi-arc ion plating technology solves the problem of insufficient thermal stability of the existing coatings in high temperature environments, and achieves efficient solar light absorption and excellent high-temperature thermal stability.
Patent Information
- Application Number
- CN202310082675.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-08
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-02-08
AI Technical Summary
The existing metal cermet photothermal conversion coatings are prone to diffusion and migration of interlayer atoms in an environment above 500°C, resulting in agglomeration, growth and oxidation of nanoparticles, which in turn triggers irreversible attenuation of the selected absorption performance and insufficient thermal stability.
The nanocomposite structural metal cermet photothermal conversion coating is prepared by multi-arc ion plating technology. The coating consists of a Cr infrared reflective layer, an AlCrON nanocomposite absorption layer and an AlCrO anti-reflective layer. The AlCrON nanocomposite absorption layer forms a multi-layer structure through alternately distributed nanoparticles and amorphous dielectrics to enhance thermal stability and select absorption performance.
Working stably in an atmospheric environment above 600°C for more than 1500 hours, the absorption rate of the coating can reach ~93% and the emissivity is only ~10%. It also has excellent high-temperature thermal stability, which can simultaneously improve the thermal stability and selective absorption performance of the coating.
Smart Images

Figure CN116083840B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of special coating preparation, and relates to a microstructure design of a high-temperature resistant metal ceramic-based photothermal conversion coating and a manufacturing method thereof. Background Art
[0002] With the continuous development of the economy and society, the demand for energy has increased dramatically, while the available non-renewable energy, such as coal, oil, natural gas and other fossil energy, is decreasing day by day, accompanied by serious environmental pollution. Therefore, the development of clean and renewable new energy is of great significance to the sustainable development of human society. Solar energy has advantages in the development and utilization of new energy due to its clean, pollution-free and huge reserves. Among them, solar thermal application is one of the simplest, most direct and most effective ways to utilize solar energy, and it has high conversion efficiency and economy, and it can also be compatible with the existing energy construction system. However, the energy density of sunlight is small and discontinuous after reaching the earth, and the photothermal conversion coating must be used to enrich the sunlight in order to maximize the use of solar energy. Therefore, the photothermal conversion coating is also recognized as the "core" of solar thermal utilization.
[0003] Photothermal conversion coating is a special coating that has a selective absorption effect on sunlight, that is, it has a high absorption ratio in the solar spectrum range (0.3-2.5μm) and a low emission ratio in the infrared band (2.5-25μm), so that it can efficiently convert sunlight into thermal energy. At the same time, with the continuous development of solar thermal utilization technology, photothermal conversion coatings must also have good thermal stability. For example, the trough solar thermal power generation system based on molten salt medium requires an operating temperature of more than 550℃. Such a high temperature will intensify the diffusion of atoms and the reaction with ambient gases, causing the photothermal conversion coating to attenuate its selective absorption performance or even completely lose it.
[0004] Among the existing photothermal conversion coatings, the metal ceramic coating formed by metal nanoparticles embedded in ceramic dielectrics can obtain a high selective absorption effect by controlling the content, size and shape of the nanoparticles, and is the most widely used photothermal conversion coating. For example, patents such as CN106167892B, CN102954611A, CN103528251B, CN102653151A, and CN109883073B have designed multi-layer metal ceramic structure photothermal conversion coatings, but their disadvantages are that when they are used for a long time in an environment above 500°C, diffusion and migration of atoms between layers are prone to occur, causing the nanoparticles in the coating to undergo unstable behaviors such as agglomeration, growth and oxidation, thereby inducing irreversible attenuation of the selective absorption performance of the coating, that is, the high-temperature thermal stability of the metal ceramic photothermal coating is insufficient. Therefore, the development of metal ceramic coatings with excellent selective absorption and thermal stability has become a technical bottleneck for the large-scale promotion of solar thermal applications.
[0005] Based on the main problems existing in the existing preparation technology, a nano-composite structure coating with simple process, strong thermal stability in atmospheric environment above 500°C, and dual regulation of spectrally selective absorption performance and thermal stability is urgently needed in the industry. Summary of the invention
[0006] In order to solve the shortcomings and deficiencies in the prior art, the present invention provides a nano-composite metal ceramic light-to-heat conversion coating, which includes a Cr infrared reflection layer, an AlCrON nano-composite absorption layer and an AlCrO anti-reflection layer from bottom to top, wherein the AlCrON nano-composite absorption layer is a typical nano-composite structure, which can stably work for more than 1500 hours in an atmospheric environment above 600°C, and the coating has an absorption rate of up to 93% for sunlight, an emissivity of only 10%, and is easy to regulate the absorption spectrum.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned nano-composite structure photothermal conversion coating; the method utilizes a multi-arc ion plating method to prepare an AlCrON nano-composite coating, and through the composition and structural design of the coating, the coating has a nano-composite multilayer structure, which is beneficial to the regulation of microstructure, physical phase and optical properties, and can integrate multiple absorption mechanisms, thereby obtaining a metal ceramic photothermal conversion coating with both high spectral selective absorption performance and thermal stability.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A composite structure metal-ceramic light-to-heat conversion coating, the coating comprising from bottom to top:
[0010] 316 stainless steel substrate, Cr infrared reflection layer, AlCrON nanocomposite absorption layer and AlCrO anti-reflection layer; wherein:
[0011] The AlCrON nanocomposite absorption layer is a nanocomposite structure formed by the deposition of AlN and CrN nanoparticles and an amorphous dielectric matrix, with a total coating thickness of 100 nm;
[0012] AlN and CrN nanoparticles are distributed in layers with a thickness of 3 to 6 nm;
[0013] The thickness of the amorphous dielectric matrix monolayer is 4 to 8 nm, and the nanoparticles and amorphous are distributed periodically;
[0014] The volume ratio of the metal ceramic component in the AlCrON nanocomposite absorption layer is 1:3 to 3:4.
[0015] The present invention also discloses a method for preparing a composite structure metal-ceramic light-to-heat conversion coating, comprising:
[0016] (1) Cleaning the substrate: The mechanically polished 316 stainless steel sheet was ultrasonically cleaned with acetone and anhydrous ethanol respectively, and then dried for later use;
[0017] (2) Vacuuming: Fix the 316 stainless steel sheet on the rotating bracket in the furnace chamber of the multi-arc ion plating equipment, close the furnace door, start the rotating bracket to spin, and heat the vacuum chamber to 200-300°C;
[0018] (3) Plasma etching cleaning: After the vacuum degree reaches the requirement, high-purity Ar is introduced and bias voltage is applied, and cleaning is carried out in a furnace chamber at 0.4-0.8 Pa for 5-10 minutes;
[0019] (4) Deposition of infrared reflective Cr: Turn on the Cr target power supply, adjust the Ar flow rate, keep the furnace chamber pressure at 0.4-0.8 Pa, apply substrate bias and maintain for 5-10 min;
[0020] (5) Deposition of AlCrON nanocomposite absorption layer: Turn on the AlCr target power supply, introduce 20-50 sccm of O2, adjust the N2 flow rate to keep the furnace chamber pressure at 0.4-0.8 Pa, apply substrate bias and maintain for 2-5 min;
[0021] (6) Deposition of AlCrO anti-reflection layer: Turn on the AlCr target power supply, introduce 100-150 sccm of O2, adjust the Ar flow rate to keep the furnace chamber pressure at 0.4-0.8 Pa, apply substrate bias and maintain for 2-5 minutes;
[0022] (7) After the deposition is completed, the arc target power supply, bias power supply, gas valve, and heating power supply are turned off in sequence. After the temperature of the vacuum chamber drops to room temperature, the furnace door is opened and the sample is taken out to obtain a composite structure metal ceramic photothermal conversion coating.
[0023] Furthermore, the ultrasonic cleaning time in step (1) is 20 to 30 minutes.
[0024] Furthermore, in step (2), the rotation speed of the rotating frame is 4 to 8 r / min; the vacuum degree of the vacuum chamber is 3.0×10 -3 ~6.0×10 -3 Pa.
[0025] Furthermore, in step (3), the purity of Ar is 100 to 200 sccm; and the applied bias voltage is -600 to -1000V.
[0026] Furthermore, in step (4), the current of the Cr target power supply is 80 to 110 A; and the applied substrate bias is -100 to -150 V.
[0027] Furthermore, in step (5), the current of the AlCr target power supply is 60 to 100 A; and the applied substrate bias is -100 to -150 V.
[0028] Furthermore, in step (6), the current of the AlCr target power supply is 60 to 100 A; and the applied substrate bias is -100 to -150 V.
[0029] The present invention also discloses a composite structure metal-ceramic light-to-heat conversion coating prepared according to any of the above preparation methods.
[0030] The present invention also discloses an application of the composite structure metal-ceramic light-to-heat conversion coating in the field of solar high-temperature heat utilization.
[0031] Principle of the invention: The invention adopts ion source assisted multi-arc ion plating technology, mainly using the uneven spatial distribution of cathode arc plasma. The ion concentration is high in the low-angle area close to the normal of the target surface, and the ion concentration is low in the high-angle area. + Due to its large mass and slow diffusion rate, Al is mainly concentrated in the space area normal to the target surface. + Small mass, fast diffusion speed, can diffuse to the target surface normal high angle area. During the deposition process, excessive gas concentration will form a complete oxide / nitride structure, and the reaction gas is not enough to completely react with Cr. + 、Al + When a reaction occurs, a composite structure of oxide / nitride and metal is formed, and by rotating the substrate, a nano-composite multilayer structure of alternating amorphous and crystalline materials is formed.
[0032] The present invention has the following advantages and effects compared with the prior art:
[0033] (1) The present invention adopts multi-arc ion plating technology, which has a simple preparation process, a fast deposition speed, and a low cost. The bonding force between the prepared coating and the substrate is strong, which helps to improve the reliability of the coating;
[0034] (2) The present invention controls the rotation of the substrate to self-assemble during the deposition process to form a nanocomposite multilayer structure in which nanocrystals and amorphous materials are alternately arranged, which significantly simplifies the preparation process of the metal-ceramic photothermal conversion coating. The deposition process is controllable and suitable for industrial production.
[0035] (3) The composite structure metal-ceramic photothermal conversion coating designed in the present invention can combine the excellent thermal stability and spectral selective absorption performance of nitride, and at the same time can inhibit the diffusion and fusion of nanoparticles, thereby achieving the simultaneous improvement of the thermal stability and selective absorption performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1The schematic diagram of the structure of the nanocomposite metal ceramic light-to-heat conversion coating prepared in Examples 1 and 2 and the experimentally measured reflection spectrum curves before and after annealing; Figure 1 (a) is a schematic diagram of the structure of the composite metal-ceramic photothermal conversion coating, 1(b) is the reflection spectrum curve of the S1 sample before and after annealing at 550°C and atmospheric conditions for 1500 hours, and 1(c) is the reflection spectrum curve of the S2 sample before and after annealing at 550°C and atmospheric conditions for 1500 hours.
[0037] Figure 2 This is the TEM image of the prepared coating after annealing at 550°C in atmospheric conditions for 1500 hours. The coating consists of a Cr infrared reflection layer, an AlCrON nanocomposite structure absorption layer, and an AlCrO anti-reflection layer. The nanoparticles and amorphous materials present an alternating periodic modulation structure. DETAILED DESCRIPTION
[0038] The content of the present invention is described in detail below in conjunction with specific embodiments and drawings, but the embodiments of the invention are not limited thereto. Unless otherwise specified, the techniques used in the embodiments are conventional means known in the art. Unless otherwise specified, the gases, equipment and methods used in the present invention are all commonly used gases, equipment and methods in the art.
[0039] Example 1
[0040] A nanocomposite metal ceramic light-to-heat conversion coating comprises three parts: a Cr infrared reflection layer, an AlCrON nanocomposite structure absorption layer and an AlCrO anti-reflection layer, which are arranged from a 316 stainless steel substrate upwards, wherein the AlCrON nanocomposite structure absorption layer comprises alternately grown nanoparticles and amorphous materials.
[0041] The thickness of the Cr infrared reflection layer is 100-150nm, the thickness of the AlCrON nanocomposite metal ceramic layer is 100-120nm, the nanoparticles are distributed in layers with a thickness of 3-6nm, the thickness of the amorphous single layer is 4-8nm, and the nanoparticles and amorphous form multiple modulation periods.
[0042] The volume ratio of AlCrON metal ceramic components is 2:3.
[0043] Preparation process: Mirror stainless steel 316 is used as the substrate, and the coating is deposited using a high vacuum multi-arc ion plating system. The Cr infrared reflection layer is deposited using a Cr target with a purity of 99.9%, and the AlCrON nanocomposite structure absorption layer and AlCrO anti-reflection layer are deposited using Al 60 Cr 40 (atomic percentage) target material for deposition.
[0044] The target size is Φ110mm×5mm, and the 316 stainless steel substrate size is 30×40×1mm.
[0045] Specific preparation process parameters: the base rotation speed is 4r / min, the furnace temperature is 200℃, the substrate bias voltage of the Cr infrared reflection layer is -100V, the current is 90A, the Ar flow rate is 80sccm, and the deposition time is 10min. The substrate bias voltage of the AlCrON nanocomposite structure absorption layer is -150V, the current is 60A, the Ar flow rate is 80sccm, the O2 flow rate is 30sccm, the N2 flow rate is 50sccm, and the deposition time is 2min. The substrate bias voltage of the AlCrO anti-reflection layer is -150V, the current is 60A, the O2 flow rate is 130sccm, and the deposition time is 2.5min.
[0046] Specific preparation process:
[0047] (1) Cleaning the substrate: The mechanically polished 316 stainless steel sheet was ultrasonically cleaned with acetone and anhydrous ethanol for 25 min respectively, and then dried for later use;
[0048] (2) Vacuuming: Fix the substrate on the rotating bracket in the furnace chamber of the multi-arc ion plating equipment, close the furnace door, start the rotating bracket to spin, set the speed to 4r / min, and draw the vacuum degree to 5.0×10 -3 Pa, and at the same time, the vacuum chamber is heated to 200°C;
[0049] (3) Plasma etching cleaning: After the vacuum degree reaches the requirement, 130 sccm of high-purity Ar is introduced, and a bias voltage of -800 V is applied. The furnace chamber pressure is 0.6 Pa, and the cleaning time is 8 min.
[0050] (4) Deposition of infrared reflective Cr: Turn on the Cr target power supply, the current is 80-110A, adjust the Ar flow rate to keep the furnace chamber pressure at 0.6Pa, apply a substrate bias voltage of -100V, and maintain for 8min;
[0051] (5) Deposition of AlCrON nanocomposite absorption layer: Turn on the AlCr target power supply, the current is 60A, pass 30sccm of O2, adjust the N2 flow rate to keep the furnace chamber pressure at 0.6Pa, apply a substrate bias voltage of -150V, and maintain for 2min;
[0052] (6) Deposition of AlCrO anti-reflection layer: Turn on the AlCr target power supply with a current of 60 A, introduce 150 sccm of O2, adjust the Ar flow rate to keep the furnace chamber pressure at 0.6 Pa, apply a substrate bias of -150 V, and maintain for 2.5 min;
[0053] (7) After the deposition is completed, the arc target power supply, bias power supply, gas valve, and heating power supply are turned off in sequence, and the sample is taken out after the temperature of the vacuum chamber drops to room temperature to obtain a composite structure metal ceramic photothermal conversion coating.
[0054] The reflectance spectra of the coatings at close to normal incidence (<10°) in the wavelength range of 200-2500nm and 2500-25000nm were tested using an ultraviolet-visible-near-infrared spectrophotometer (Agilent Cary 5000) and a Fourier transform infrared spectrometer (Nicolet iS50 FT-IR), respectively.
[0055] The absorptivity α of the coating is calculated using the following formula:
[0056]
[0057] Where λ is the wavelength, I sol (λ) is the solar radiation power at AM1.5; I b (λ) is the blackbody radiation power at room temperature; R(λ) is the reflectivity of the coating.
[0058] The absorptivity ε of the coating is calculated using the following formula:
[0059]
[0060] The calculated absorptivity of the deposited nanocomposite structure coating is 0.903 and the emissivity is 0.145. Figure 1 (b) as shown.
[0061] The prepared coating samples were annealed in a muffle furnace at 550°C in atmospheric conditions for 1500 h.
[0062] The absorptivity and emissivity of the annealed samples were measured.
[0063] The calculated absorptivity of the deposited nanocomposite structure coating is 0.923 and the emissivity is 0.122. Figure 1 As shown in (b), the coating prepared by the present invention can absorb 92.3% of sunlight, while the thermal radiation is only 12.2%, thus achieving efficient absorption of sunlight.
[0064] TEM analysis was performed on the annealed samples. Figure 2 As shown, the microstructure of the coating presents a layered periodic structure and exhibits excellent high-temperature thermal stability, which can meet the requirements of service at 550°C and atmospheric conditions.
[0065] Example 2
[0066] The preparation method of the photothermal conversion coating described in Example 2 is basically the same as that in Example 1, the main difference being that the gas flow rate introduced during the coating preparation process is different. The specific process parameters are shown in Table 1.
[0067] Table 1 Gas flow rate and volume ratio of metal ceramic components in Examples 1 and 2
[0068]
[0069]
[0070] The photothermal conversion coating obtained in Example 2 is basically the same as that in Example 1, and the main difference lies in the volume ratio of the metal ceramic component, as shown in Table 1 for details.
[0071] The calculated absorptivity of the deposited nanocomposite structure coating is 0.908 and the emissivity is 0.152. Figure 1 As shown in (c), the coating prepared by the present invention can absorb 90.8% of sunlight, while the thermal radiation is only 15.2%, thus achieving efficient absorption of sunlight.
[0072] The prepared coating samples were annealed in a muffle furnace at 550°C in atmospheric conditions for 1500 h.
[0073] The calculated absorptivity of the annealed nanocomposite coating is 0.932 and the emissivity is 0.126. Figure 1 As shown in (c), it exhibits excellent high-temperature thermal stability and is capable of meeting the requirements of service at 550°C and atmospheric conditions.
[0074] Comparative Example
[0075] The preparation method of the photothermal conversion coating described in the comparative example is basically the same as that of Examples 1 to 2, the main difference being that the flow rates of the gases introduced during the preparation process are different. In the comparative example, the gas flow rate for depositing the Cr infrared reflective layer is: Ar 100 sccm, the gas flow rate for depositing the AlCrON nanocomposite structure absorption layer is: Ar flow rate is 90 sccm, O2 flow rate is 40 sccm, N2 flow rate is 30 sccm, and the gas flow rate for depositing the AlCrO anti-reflection layer is: O2 flow rate is 140 sccm.
[0076] The above-mentioned embodiments 1 to 2 are preferred embodiments of the present invention, but the implementation methods of the present invention are not limited to the above-mentioned embodiments. Other changes, simplifications, and substitutions that do not deviate from the essence and principles of the present invention should be regarded as equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A composite structure metal-ceramic light-to-heat conversion coating, the coating comprising from bottom to top: 316 stainless steel substrate, Cr infrared reflection layer, AlCrON nanocomposite absorption layer and AlCrO anti-reflection layer; wherein: The AlCrON nanocomposite absorption layer is a nanocomposite structure formed by the deposition of AlN and CrN nanoparticles and an amorphous dielectric matrix, with a total coating thickness of 100 nm; AlN and CrN nanoparticles are distributed in layers with a thickness of 3 to 6 nm; The thickness of the amorphous dielectric matrix monolayer is 4-8 nm, and the nanoparticles and amorphous are distributed periodically; The volume ratio of metal ceramic components in the AlCrON nanocomposite absorption layer is 1:3~3:4; The composite structure metal-ceramic light-to-heat conversion coating is prepared by the following method: (1) Cleaning the substrate: The mechanically polished 316 stainless steel sheet was ultrasonically cleaned with acetone and anhydrous ethanol respectively, and dried to obtain a 316 stainless steel substrate for use; (2) Vacuuming: Fix the 316 stainless steel substrate on the rotating bracket in the furnace chamber of the multi-arc ion plating equipment, close the furnace door, start the rotating bracket to spin, and heat the vacuum chamber to 200~300℃; (3) Plasma etching cleaning: After the vacuum degree reaches the requirement, high-purity Ar is introduced and bias voltage is applied, and cleaning is carried out in a furnace chamber at 0.4~0.8Pa for 5~10min; (4) Deposition of infrared reflective Cr: Turn on the Cr target power supply, adjust the Ar flow rate, keep the furnace chamber pressure at 0.4~0.8Pa, apply substrate bias and maintain for 5~10min; (5) Deposition of AlCrON nanocomposite absorption layer: Turn on the AlCr target power supply, introduce 20-50 sccm of O2, adjust the N2 flow rate to keep the furnace chamber pressure at 0.4-0.8 Pa, apply substrate bias and maintain for 2-5 min; (6) Deposition of AlCrO anti-reflection layer: Turn on the AlCr target power supply, introduce 100-150 sccm of O2, adjust the Ar flow rate to keep the furnace chamber pressure at 0.4-0.8 Pa, apply substrate bias and maintain for 2-5 min; (7) After the deposition is completed, the arc target power supply, bias power supply, gas valve, and heating power supply are turned off in sequence. After the temperature of the vacuum chamber drops to room temperature, the furnace door is opened and the sample is taken out to obtain a composite structure metal ceramic photothermal conversion coating.
2. The composite structure metal-ceramic light-to-heat conversion coating according to claim 1, wherein: The ultrasonic cleaning time in step (1) is 20 to 30 minutes.
3. The composite structure metal-ceramic light-to-heat conversion coating according to claim 1, wherein: The rotating speed of the rotating frame in step (2) is 4-8 r / min; The vacuum degree of the vacuum chamber is .
4. The composite structure metal-ceramic light-to-heat conversion coating according to claim 1, wherein: The Ar flow rate in step (3) is 100-200 sccm; The applied bias voltage is -600~-1000V.
5. The composite structure metal-ceramic light-to-heat conversion coating according to claim 1, wherein: The current of the Cr target power supply in step (4) is 80-110A; The applied substrate bias is -100~-150V.
6. The composite structure metal-ceramic light-to-heat conversion coating according to claim 1, wherein: The current of the AlCr target power supply in step (5) is 60-100A; The applied substrate bias is -100~-150V.
7. The composite structure metal-ceramic light-to-heat conversion coating according to claim 1, wherein: The current of the AlCr target power supply in step (6) is 60-100A; The applied substrate bias is -100~-150V.
8. An application of the composite structure metal ceramic photothermal conversion coating according to any one of claims 1 to 7 in the field of solar high-temperature thermal utilization.
Citation Information
Patent Citations
Solar selective absorption coating
CN102653151A
Medium-high temperature spectrum selective absorbing coating
CN102954611A
High-Temperature Resistant Metal-Ceramic Solar Selective Absorption Coating and Preparation Method
CN103528251B
A bimetal / ceramic composite film and its preparation method
CN106167892B
Quasi-optical microcavity structure solar spectral selective absorption coating and its preparation method
CN109883073B